ANALISIS FAKTOR FAKTOR (ROI, ARUS KAS INVESTASI DAN DER), YANG MEMPENGARUHI HARGA SAHAM PADA PERUSAHAAN MANUFACTURING DI BURSA EFEK INDONESIA (BEI) - INDAH SARI LIZA LUBIS (LP2MTBM MAKARIOZ, 2020)
The present study is a survey research with quantitative approach. Objects in this study are data on Return on Investment,Cash Flow Investments and Debt to Equity Ratio and the effect of stock prices obtained from financial statements OnManufacturing Companies listed on the Indonesia Stock Exchange Year 2014-2016. The population included 120 companiesin manufacturing companies listed on the BEI in 2014-2016. Samples are 11 companies (11 x 3 years = 33) Manufacturingcompanies listed on the Indonesia Stock Exchange. Methods of data collection using secondary data obtained fromwww.idx.co.id. www.e-bursa.com, www.yahoo.finance.com. The collected data were then analyzed by a multiple linearregression analysis. The result of the study showed that Return on Investment, Cash Flow of investment and Debt to EquityRatio simultaneously have a significant effect on stock price. This is indicated by the F-count value (5.933)> F-table(2.93404) and sig-p (0.003) <0.05. Return on investment (ROI) partially significant effect on stock prices. This is indicated bythe value of t-count value X1 (11.573)> t-table (2.04523) and p-value (0.000) <0.05. The investment cash flow is partiallysignificant effect on stock price. This is indicated by the value of t-arithmetic X2 (2.110)> t-table (2.04523) and p-value(0.043) <0.05. Debt to Equity Ratio partially have a significant and positive effect on stock price. This is indicated by thevalue that t-hit X3 (10.055)> t-table (2.04523) and p-value (0.000) <0.05. The magnitude of the influence of Return onInvestment, Cash Flow investment, Debt to Equity Ratio and Return on Investment to the Share Price is equal to 38%. It issuggested that manufacturing company listed on the Indonesia Stock Exchange can provide convenience in the form offinancial statement information so that research activities undertaken by the students can be further simplified. It is suggesedthat the next researcher do a similar research by adding another variable so that the results obtained research that serve asa reference comparison against previous research.